Labor Market Transformation: Implications of Technological Change in Society 5.0 - Khoerulloh, Abd. Kholik; Aziz, Holis Abdul (Jurnal Ilmu Ekonomi Terapan, 2024)
Society 5.0 is resulting in transformation across a wide range of sectors, including manufacturing, education, healthcare, and services. Through the adoption of artificial intelligence, machines can carry out tasks that previously could only be performed by humans, resulting in significant changes in the types of jobs and skills available in the labor market. This research aims to detail and identify how technological changes affect the labor market, as well as explore solutions and strategies to capitalize on opportunities and deal with challenges that arise from these changes for society's overall well-being. This research uses a literature study method with a predictive approach. The results showed that in the era of Society 5.0, people must improve their skills through education and training to adapt to the changes. Cross-sectoral cooperation between the government, the private sector, and the community is crucial. Joint efforts to formulate supportive policies and innovation in creating new sustainable jobs are vital to mitigating the negative impacts and harnessing the positive potential of technological change in the labor market. This research is expected to have a significant impact, ranging from policy development to improving social welfare, by comprehensively understanding how technology affects life and work in modern society.